2023
DOI: 10.1108/ebr-03-2022-0044
|View full text |Cite
|
Sign up to set email alerts
|

Integrated reporting, audit quality: presence of environmental auditing in an international context

Abstract: Purpose This paper aims to investigate the effect of audit quality and environmental auditing on integrated reporting and the effect of environmental auditing on audit quality. Design/methodology/approach Data was collected from a sample of 300 international companies during the period 2010–2019. The author collected the data from the Thomson Reuters Eikon database, sustainability reports and annual reports. A multiple regression analysis was performed to test the hypotheses. Findings The finding of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 137 publications
0
6
0
Order By: Relevance
“…There are also few service articles that measure the environmental impacts of services, although the quantification of environmental impacts arises in the non-service domain. For example, the literature in accounting discusses the measurement of firms’ environmental impact (Vitolla et al , 2019; Hichri, 2023; Niemenmaa, 2022). Environmental auditing and management services are explored in non-business journals, such as Ecosystem Services (e.g.…”
Section: Current Service Research and Sdgs #6 #7 And #12mentioning
confidence: 99%
“…There are also few service articles that measure the environmental impacts of services, although the quantification of environmental impacts arises in the non-service domain. For example, the literature in accounting discusses the measurement of firms’ environmental impact (Vitolla et al , 2019; Hichri, 2023; Niemenmaa, 2022). Environmental auditing and management services are explored in non-business journals, such as Ecosystem Services (e.g.…”
Section: Current Service Research and Sdgs #6 #7 And #12mentioning
confidence: 99%
“…Using the U.S. data, Sun et al found that firms with higher CSR performance are more likely to engage industry specialist auditors [56]. Using international evidence, Hichri found a positive association between audit quality and integrated reporting [57]. Using U.S. data, Du et al found that companies with higher CSR performance are likely to engage big (high-quality) auditors [52].…”
Section: Corporate Social Responsibility (Csr) and Auditor Choicementioning
confidence: 99%
“…According to the ethical perspective, firms committed to ESG practices are likely to be honest and trustworthy by having a strict code of ethics [57] that, in turn, would restrict reporting irregularities [60], and instead support transparency of financial reports and information quality [51,61]. Supporting this view, some studies revealed that firms' ESG practices are related to lower misstatement and client business risk [60,62].…”
Section: Esg Performance and Audit Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory environment and oversight mechanisms significantly impact audit quality, as stringent regulations and effective oversight contribute to a more robust auditing process [ 8 ]. Technological advancements and the adoption of innovative audit tools have emerged as crucial factors shaping audit quality in the contemporary business landscape [ 9 ]. Understanding the intricate interplay of these factors is essential for advancing research and enhancing the overall quality and effectiveness of auditing practices.…”
Section: Introductionmentioning
confidence: 99%